2017
DOI: 10.2217/3dp-2016-0007
|View full text |Cite
|
Sign up to set email alerts
|

3D-Printed Smartphone-Based Device for Label-Free Cell Separation

Abstract: Aim: To assess several fabrication metrics of a 3D-printed smartphone-attachable continuous-flow magnetic focusing device for real-time separation and detection of different cell types based on their volumetric mass density in high-volume samples. Method: The smartphone apparatus has been designed and fabricated using three different 3D printing method. Several 3D printing metrics including cost, printing time, and resolution have been evaluated to propose a cost-efficient and high-performance platform for low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…It should also be noted that the paramagnetic solutions used here are limited by the range of density liquids they can detect. However, it has been shown that the range can be shifted by changing the density of the paramagnetic medium and it can be expanded by increasing the concentration of the paramagnetic medium [16][17][18][19][20].…”
Section: Resultsmentioning
confidence: 99%
“…It should also be noted that the paramagnetic solutions used here are limited by the range of density liquids they can detect. However, it has been shown that the range can be shifted by changing the density of the paramagnetic medium and it can be expanded by increasing the concentration of the paramagnetic medium [16][17][18][19][20].…”
Section: Resultsmentioning
confidence: 99%
“…The custom-designed case of our fluorescence reader was 3D-printed using black thermoplastic material. After capturing the fluorescence image, a custom-designed smartphone application wirelessly transmits the image to a server (which could also be a local computer or laptop) for rapid and automated quantification of the ion concentrations [33][34][35][36] . The images are processed using a custom-developed algorithm and the concentration measurement of each ion in the sample of interest is returned back to the smartphone within ~ 90 s, and is displayed to the user through the same smartphone application.…”
Section: Design and Fabrication Of Smartphone-enabled Readermentioning
confidence: 99%
“…Magnetic levitation has been an attractive tool for researchers from a variety of disciplines in life sciences 11 due to its simplicity, cost-effectiveness and minimal effort for processing of the sample but above all, major advantages is to provide label-free separation of target cells in a heterogeneous solution. So far, a wide range of applications including label-free separation of malaria-infected red blood cells, sickle cells 12 , blood 12,13 , tumor cells 8,13 , adipocytes 14 , and cardiomyocytes 15 , realization of microparticle-based immunoassays 16,17 and biofabrication of cells [18][19][20] have been achieved by applying magnetic levitation technology.…”
Section: Density Differences Within Cell Populations May Occur Based mentioning
confidence: 99%